Accounting Teachers’ Voices on Factors Affecting Online Teaching during the 4th Industrial Revolution in the Face of COVID-19 in Selected High Schools in the Eastern Cape, South Africa - Melikhaya Skhephe; Christabel Mantlana (Research in Social Sciences and Technology, 2021)
The most prominent debate in South Africa is how teachers will provide instruction online. The purposes of this article was to explore Accounting teachers’ voices on factors affecting online teaching. To this end, the researchers employed a qualitative approach and a case study research design. Interviews were used as a method to collect data from 10 Accounting teachers who were purposively selected. Thematic data analysis was used. The results revealed that, Accounting teachers are lacking required knowledge and skills needed to facilitate technology learning in their classrooms. Results further reveal that, online teaching arrived at an awkward moment when teachers were faced with COVID-19 pandemic. The study concludes that teachers’ voices play an important role in any proposed changes in the classroom. The Eastern Cape Province where the study was conducted should quickly roll out infrastructure at all schools aiming to support online classrooms. It is recommended in this paper that teachers need to be workshopped in online teaching in order for them to perform effectively.